Role of 11β-hydroxysteroid dehydrogenase 2 renal activity in potassium homeostasis in rats with chronic renal failure - Yeyati, Nesmo (2010)
Aldosterone concentrations vary in advanced chronic renal failure (CRF). The isozyme 11β-hydroxysteroid dehydrogenase 2 (11β-HSD2), which confers aldosterone specificity for mineralocorticoid receptors in distal tubules and collecting ducts, has been reported to be decreased or normal in patients with renal diseases. Our objective was to determine the role of aldosterone and 11β-HSD2 renal microsome activity, normalized for glomerular filtration rate (GFR), in maintaining K+ homeostasis in 5/6 nephrectomized rats. Male Wistar rats weighing 180-220 g at the beginning of the study were used. Rats with experimental CRF obtained by 5/6 nephrectomy (N = 9) and sham rats (N = 10) were maintained for 4 months. Systolic blood pressure and plasma creatinine (Pcr) concentration were measured at the end of the experiment. Sodium and potassium excretion and GFR were evaluated before and after spironolactone administration (10 mg·kg-1·day-1 for 7 days) and 11β-HSD2 activity on renal microsomes was determined. Systolic blood pressure (means ± SEM; Sham = 105 ± 8 and CRF = 149 ± 10 mmHg) and Pcr (Sham = 0.42 ± 0.03 and CRF = 2.53 ± 0.26 mg/dL) were higher (P < 0.05) while GFR (Sham = 1.46 ± 0.26 and CRF = 0.61 ± 0.06 mL/min) was lower (P < 0.05) in CRF, and plasma aldosterone (Pald) was the same in the two groups. Urinary sodium and potassium excretion was similar in the two groups under basal conditions but, after spironolactone treatment, only potassium excretion was decreased in CRF rats (sham = 0.95 ± 0.090 (before) vs 0.89 ± 0.09 µEq/min (after) and CRF = 1.05 ± 0.05 (before) vs 0.37 ± 0.07 µEq/min (after); P < 0.05). 11β-HSD2 activity on renal microsomes was lower in CRF rats (sham = 0.807 ± 0.09 and CRF = 0.217 ± 0.07 nmol·min-1·mg protein-1; P < 0.05), although when normalized for mL GFR it was similar in both groups. We conclude that K+ homeostasis is maintained during CRF development despite normal Pald levels. This adaptation may be mediated by renal 11β-HSD2 activity, which, when normalized for GFR, became similar to that of control rats, suggesting that mineralocorticoid receptors maintain their aldosterone selectivity.